Membangun Media Massa Publik dalam Menanamkan Pendidikan Karakter - Oos M Anwas (Jurnal Pendidikan dan Kebudayaan, 2011)
In the information era, character education is necessary to be done through mass media. Privately-controlled mass media is often marred by ideological and owner’s interests as well as by financial benefits. Therefore we need a public mass media with public interest idealism. It could be in the form of public newspaper, public magazine, public radio, public television, or public web/portal. To be able to instill character education, substance of the public mass media should be designed in accordance with the needs and character of the target, distributed continuously, easily accessed or utilized by the target, and packaged in an attractive format to enable it to compete with other mass media. The substance is required to encourage and create a community of learners, inspire, educate, and provide examples in building the nation’s character. To realize that the public mass media can be developed from existing institutions such as RRI, TVRI, or Antara News Agency in a synergistic manner with all potential in ministries or other institutions in the aspect of substance, infrastructure, human resources, etc.